(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to demonstrate the relationship between tax reform policies and foreign investment, as tax policies are considered one of the main factors that affect the attraction of foreign investments, and tax amendments can affect the decisions of foreign investors. Countries seek to improve the business environment by adopting more flexible and competitive tax policies. The research deals with a sample of data related to foreign investment in Iraq during the period from 2018 to 2022, where the impact of changes in tax policies on foreign investment levels was analyzed. This research aims to demonstrate how tax policies can contribute to enhancing economic growth by attracting foreign investment. This research highlights the importance of tax policies in encouraging companies to adopt sustainable practices, which contributes to improving the public image of investors and attracting investments that focus on social responsibility. The research explains how amending tax rates can make them more attractive to investors. This research seeks to clarify the role of tax exemptions in attracting new investments. Finally, the research shows the importance of establishing agreements with other countries to protect foreign investments. One of the most important results of the research is that it contributes to consolidating the work of the General Tax Authority and the National Investment Authority by improving the business environment and increasing foreign investment flows, with a focus on how tax reforms affect improving the investment climate and attracting foreign capital. This research is expected to provide important insights into how to enhance tax policies to attract more foreign investment in the future, which enhances the effectiveness of economic policies in Iraq.